Finance and Development, December 1976. (Finance and Development; Finance and Development, 1976)
This paper highlights that the World Bank and its affiliate, the International Development Association (IDA), will support three projects in Kenya-one for rural access roads, an additional for integrated rural development, and a third for wildlife and tourism. A USD 4 million loan and a USD 4 million IDA credit will assist the government of Kenya in implementing the first phase of the rural access roads program. The program aims at the construction of 15,000 km of rural access roads in eight years.